Leave and financial support for family caregivers in EU member states - Hoyer, Sören; Reich, Nele (Frankfurt a. M., 2016)
This report shows which forms of long-term leave exist in several EU member states for family caregivers who care for a dependent relative at home. It also shows, whether there is some form of financial benefit available for the caregiver during the leave. The support arrangements of 14 member states of the European Union (EU) are presented in brief descriptions and overview tables.
Keywords: Europäische Union; Sorgearbeit; Familie; Recht; Sozialleistung; 300 Sozialwissenschaften